Factors Influencing The Acceptance of ChatGPT for Students: Analysis of UTAUT2 Framework with Personal Innovativeness - Pasaribu, Popy Novita; Abidin, Zainal; Putri, Melda Amelia (Diversity: Jurnal Ilmiah Pascasarjana, 2025)
ChatGPT has advanced significantly across various sectors, including education. The growing interest and potential acceptance of ChatGPT among students highlight the importance of understanding learners’ perceptions. This study examines variables influencing student adoption and use of ChatGPT, particularly in education. The analysis uses the UTAUT 2 model combined with the PI (Personal Innovativeness) aspect. The factors studied are EE (Effort Expectancy), PE (Performance Expectancy), H (Habit), FC (Facilitating Condition), HM (Hedonic Motivation), and PI toward BI (Behavioral Intention). Data were collected from 101 respondents and quantitative data analysis using IBM SPSS Statistics 27. At the initial stage, the overall influence of all independent variables on BI was tested using the F-test. Then, the partial influence of each independent variable (EE, PE, H, FC, HM, PI) was tested using the T-test. A one-way ANOVA was used to compare BI based on respondent attributes, namely gender (G) and education level (EL). The findings indicated that PE and H are most influential variables on the intention to use ChatGPT. EE, FC, HM, and PI have no significant partial effects. Nevertheless, BI will still impact with 68% when all variables are combined. Gender and education level do not show significant differences in behavioral intention.